Hermann Czech An Architect in Vienna - Kuss, Eva (2023)
The present book documents, analyzes and interprets the background and career as well as the works of Hermann Czech, probably the most important living architect and architectural theorist in Austria. An introductory section on Viennese Modernism is followed by a detailed narrative of Czech's childhood, youth, and training period, from which the architect's personal and professional development can be understood; an important element here is the - abstracted - form of speech and counter-speech by the architect and the author. An essay by the philosopher Elisabeth Nemeth is followed by the work section, in which more than thirty projects are presented in detail and placed in context; an extensive appendix completes the book.